Dynamics of Messianic Movements in Africa. Case study of the population of Lower Congo Basin - Pawlik, Jacek Jan (Studia Warmińskie, 2020)
The article deals with churches and religious groups that arose in Africa on the basis of Christianity in the 20th century, taking as example the case of the Lower Congo Basin. Initially, it was a protest against racial segregation and colonial exploitation. Emerging independent churches were often a forge of nascent nationalisms. Enlivened by a messianic spirit, they promised a better future with independence. Over time, these churches institutionalized and gained independence, but this did not mean the promised bright reality. On the contrary, the crisis of the 1980s and 1990s has increased poverty and challenged existing development. New neo-Pentecostal religious movements that preach theology of prosperity and practical salvation are developing on this ground of poverty. They preach that it is possible to get out of poverty only through personal conversion and religious commitment. Due to the great popularity of these movements, independent African churches were forced to adapt significantly.